The Effect of a Service Provider's Competitive Market Position on Churn Among Flat-Rate Customers. (August 2018) - Moser, Sabine; Schumann, Jan H.; von Wangenheim, Florian; Uhrich, Fabian; Frank, Felix
Flat-rate pricing, as opposed to charging customers for actual usage, dominates many service industries (e.g., telecommunications, health clubs, and music streaming), and customers often express a flat-rate bias and choose flat rates even if a pay-per-use tariff would be less expensive for them. However, evidence of the effect of this bias on churn is mixed. The competitive market position of a service provider may represent a relevant contingency factor related to this effect; building on attribution theory, the current study predicts that customers attribute their flat-rate bias differently, depending on service providers' strategic positioning, which leads to varying churn behavior. A survival analysis of approximately 2 years' transactional data gathered from 21, 490 customers of a premium Internet service provider affirms that a flat-rate bias leads to churn in the premium segment. Two experimental studies show that customers of premium service providers attribute their flat-rate bias more externally and exhibit lower fairness perceptions but increased churn intentions compared to low-cost customers who make internal attributions and who thus have less negative perceptions and lower churn intentions. Therefore, premium service managers must proactively manage customers who exhibit flat-rate biases to prevent their negative reactions. Low-cost providers generally have less need for such action and can benefit from flat rates without risking increased churn, despite higher price sensitivity of their customers.